Methods for assessment of pre‑harvest sprouting in wheat cultivars - Gavazza, Melicia Ingredi Araújo; Bassoi, Manoel Carlos; Carvalho, Tereza Cristina de; Bespalhok Filho, João Carlos; Panobianco, Maristela (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to test methods for pre‑harvest sprouting assessment in wheat cultivars. Fourteen wheat cultivars were grown in Londrina and Ponta Grossa municipalities, Paraná state, Brazil. They were sampled at 10 and 17 days after physiological maturity and evaluated using the methods of germination by rainfall simulation (in a greenhouse), in‑ear grain sprouting, and grains removed from the ears. The in‑ear grain sprouting method allowed the differentiation of cultivars, but showed different resistance levels from the available description of cultivars. The sprouting of grain removed from the ears did not allow a reliable distinction of data on germination in any harvest date or location. The method of rainfall simulation is the most suitable for the assessment of cultivars as to pre‑harvest sprouting, regardless of the sampling date and evaluated location.
Keywords: Triticum aestivum; dormancy; grain quality; rainfall simulation.